Perancangan dan pembangunan pusat pertumbuhan desa : PPD Kedah - Rosmin Talib; Katiman Rostam (Selangor : Penerbit Universiti Kebangsaan Malaysia, 2014)
A study on economic development and community development in rural area in state of Kedah, Malaysia.
Rujukan : mukasurat 329-342.
In Malay.
Keywords: Rural development -- Malaysia -- Kedah; Community development -- Malaysia -- Kedah; Economic development projects -- Kedah